2009
DOI: 10.3329/jhpn.v26i4.1884
|View full text |Cite
|
Sign up to set email alerts
|

Increased Isolation and Characterization of <i>Shigella sonnei</i> Obtained from Hospitalized Children in Tehran, Iran

Abstract: Shigella flexneri has been the most frequent cause of shigellosis in children in Iran. To evaluate the changes in frequency of serogroups, 302 Shigella species were isolated in 2003 from hospitalized children, aged less than 12 years, with acute diarrhoea in Tehran, Iran. The number of collected S. sonnei, S. flexneri, S. boydii, and S. dysenteriae isolates was 178 (58.9%), 110 (37.4%), 10 (3.3%), and 4 (1.3%) respectively. Most (94%) S. sonnei isolates were resistant to co-trimoxazole. They were, however, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
3
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 18 publications
3
17
3
2
Order By: Relevance
“…In a recent study all S. boydii strains were categorized into two patterns only. Moreover, all but one isolates, belonged to ribotype I (Ranjbar et al, 2008). However, this finding is similar to recent reports from other developing countries, such as Bangladesh (Talukder et al, 2006b).…”
Section: Ribotyping In Shigella Isolatescontrasting
confidence: 37%
See 1 more Smart Citation
“…In a recent study all S. boydii strains were categorized into two patterns only. Moreover, all but one isolates, belonged to ribotype I (Ranjbar et al, 2008). However, this finding is similar to recent reports from other developing countries, such as Bangladesh (Talukder et al, 2006b).…”
Section: Ribotyping In Shigella Isolatescontrasting
confidence: 37%
“…Nastasi and colleagues have also found 13 ribotypes by examining 432 S. sonnei isolates (Nastasi et al, 1993). Ranjbar et al (Ranjbar et al, 2008) observed a single ribotype pattern among the S. sonnei isolates collected in Tehran.…”
Section: Ribotyping In Shigella Isolatesmentioning
confidence: 99%
“…Recently, other reports have also indicated the increasing resistance to streptomycin and cotrimoxazole among Shigella spp. in Iran and other countries (Ranjbar et al, 2008;Seol et al, 2006;Vrints et al, 2009). …”
Section: Discussionmentioning
confidence: 95%
“…in developing countries while in Europe and North America S. sonnei is predominant and is a reflection of standards of living (1994). In the last decades several reports have revealed that the majority of shigellosis in Iran is caused by S. flexneri but in recent years a growing tendency has been observed toward S. sonnei (Farshad et al, 2006;Ranjbar et al, 2008). Increasing incidence of S. sonnei versus S. flexneri may imitate the industrialization of the capital city and the improving hygiene level in Iran (Ranjbar et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…higella sonnei has emerged as a major global cause of shigellosis (1)(2)(3)(4)(5). There are 4 distinct S. sonnei lineages, and the current global burden involves several geographically associated, multidrug-resistant clones that belong to a single lineage (1).…”
mentioning
confidence: 99%